Invisible Pain, Visible Inequalities: Gender, Social Agency, and the Health of Women with Fibromyalgia - Gonzalez-Droguett, N (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: Fibromyalgia (FM) is a chronic nociplastic pain condition predominantly affecting women. Although often addressed within biomedical frameworks, its structural and relational dimensions remain underexplored. This study examined how social, familial, and economic factors are associated with symptom severity and self-perceived mental health among women with FM, with particular emphasis on social participation and perceived discrimination. Methods: A cross-sectional study was conducted among women diagnosed with FM in Chile. Participants were recruited through patient organizations and community networks and completed a self-administered questionnaire covering biopsychosocial aspects of FM. Multifactor ANOVA models were used to explore associations between social and familial variables and symptom count and perceived mental health. Results: Participants were mostly middle-aged women who reported a high burden of symptoms and moderate levels of self-perceived mental health. Involvement in FM-related organizations was significantly associated with differences in symptom perception and better mental health, while perceived discrimination was linked to poorer mental health outcomes. Conclusions: Social participation and supportive environments emerge as potential determinants of health among women with FM. Primary care providers should adopt social and gender-sensitive approaches that acknowledge the influence of discrimination, economic vulnerability, and support networks in shaping the illness experience. © 2025 by the authors.